Bills of Fare, Consumer Demand, Social Status, Ethnicity, and the Collapse of California Abalone. Issue Volume 41:Issues 2(2021) (July 2021) - Braje, Todd J.; Bentz, Linda
Since at least the mid-nineteenth century, California's Pacific Coast has been an epicenter of global commercial fishing activities. Decades of intensive harvest, pollution, anthropogenic climate change, and disease, however, have resulted in the collapse of many of the state's most important and profitable fisheries. Much of the research designed to understand the processes and consequences of this crisis of the oceans has focused on production issues—the number of fish that live in and are harvested from the ocean. Here, we turn our attention to consumption issues and explore how market-forces, status, ethnicity, and evolving perceptions of food can drive fisheries collapse. We use the rise and fall of the California abalone ( Haliotis spp.) fishery as a case study and compile data on the price of abalone dishes from bills of fare, primarily in southern California, dating between 1901 and 2005. We explore how and why restaurant prices for abalone dishes changed over the last century and the role of consumer demand (or taste) and social status in influencing the health and stability of fish stocks.